- #1

- 798

- 1

## Main Question or Discussion Point

Hello all,

I'm trying to find the derivation for the alternating signal. For example,

let b=width of loop

a=length of loop

Hence,

[tex]ε=vLB=vaB=ωraB=\frac{1}{2}ωabB=\frac{1}{2}ωAB[/tex]

I cannot seem to find the derivation of how one gets from this step, to the sinusoidal waveform. Any help is greatly appreciated.

I'm trying to find the derivation for the alternating signal. For example,

let b=width of loop

a=length of loop

Hence,

[tex]ε=vLB=vaB=ωraB=\frac{1}{2}ωabB=\frac{1}{2}ωAB[/tex]

I cannot seem to find the derivation of how one gets from this step, to the sinusoidal waveform. Any help is greatly appreciated.